Clouds of witnesses : Christian voices from Africa and Asia - Noll, Mark A., 1946-; Nystrom, Carolyn (Downers Grove, Ill. : IVP Books, 2011)
In seventeen narratives Mark Noll and Carolyn Nystrom introduce Christian leaders in Africa and Asia who had tenacious faith in the midst of deprivation, suffering and conflict. Spanning a century, from the 1880s to the 1980s, their stories demonstrate the vitality of the Christian faith in a diversity of contexts.
Southern Africa -- Bernard Mizeki (c. 1861-1896) : the first Anglican African martyr -- John Chilembwe (c. 1870-1915) : holistic Christian and accidental rebel -- Albert Luthuli (1898-1967) : gentleman of justice -- West Africa -- William Wadé Harris (c. 1865-c. 1929) : passionate prophet -- Byang Kato (1936-1975) : theological visionary -- East Africa -- Simeon Nsibambi (1897-1978) : revival anchor -- Janani Luwum (1922-1977) : martyr of "the second century" -- India -- Pandita Ramabai (1858-1922) : Christian, Hindu, reformer -- V.S. Azariah (1874-1945) : bishop, statesman, pastor -- Sundar Singh (1889-1929?) : mysterious mystic -- Korea -- Sun Chu Kil (1869-1935) : pastor and founding father -- China -- Dora Yu/Yu Cidu (1873-1931) : catalyst for an enduring Chinese faith -- Mary Stone/Shi Meiyu (1873-1954) : agent of change -- John Sung/Song Shangjie (1901-1944) : firestorm evangelist -- Yao-Tsung Wu/Wu Yaozong (1893-1979) : communist and Christian -- Wang Mingdao (1900-1991) : imprisoned by choice -- Ignatius Cardinal Kung/Kung Pin-Mei (1901-2000) : a Catholic valiant for truth.
Includes bibliographical references and index.
Keywords: Christian biography -- Asia; Christian biography -- Africa; Asia -- Church history -- 20th century; Africa -- Church history -- 20th century